Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 130472 by shaker last updated on 26/Jan/21

Answered by mathmax by abdo last updated on 26/Jan/21

let w(x) =Σ_(k=1) ^n (2k−1)x^k  ⇒w(x)=2Σ_(k=1) ^n  kx^k −Σ_(k=1) ^n  x^k   we have Σ_(k=0) ^n  x^k  =((x^(n+1) −1)/(x−1))  (x≠1) ⇒Σ_(k=1) ^n  kx^(k−1)  =((nx^(n+1) −(n+1)x^n +1)/((x−1)^2 ))  ⇒Σ_(k=1) ^n kx^k  =(x/((x−1)^2 ))(nx^(n+1) −(n+1)x^n  +1) ⇒  w(x)=((2x)/((x−1)^2 ))(nx^(n+1) −(n+1)x^n +1)−((1/(1−x))−1)  =((2x(nx^(n+1) −(n+1)x^n +1))/((x−1)^2 ))−((x(1−x))/((1−x)^2 ))  =((2x(nx^(n+1) −(n+1)x^n  +1)+x^2 −x)/((x−1)^2 )) ⇒  f(x)=(((√(2nx^(n+2) −2(n+1)x^(n+1) +x^2  +x))×(1/(x−1))−n)/((x−1)))  =(((√(2nx^(n+2) −2(n+1)x^(n+1) +x^2  +x))−n(x−1))/((x−1)^2 )) we do the changement  x−1=t  (t→0) ⇒f(x)=f(t+1)  =(((√(2n(t+1)^(n+2) −2(n+1)(t+1)^(n+1) +(t+1)^2  +t))−nt)/t^2 )  we have (1+t)^(n+2)  ∼1+(n+2)t +(((n+2)(n+1))/2)t^2   (1+t)^(n+1) ∼1+(n+1)t+(((n+1)n)/2)t^2   (t+1)^2  +t ∼1 ⇒  2n(t+1)^(n+2) −2(n+1)(t+1)^(n+1) +(t+1)^2  +t  ∼2n{1+(n+2)t+(((n+2)(n+1))/2)t^2 }−2(n+1)(1+(n+1)t+(((n+1)n)/2)t^2 )+1  ....be continued...

letw(x)=k=1n(2k1)xkw(x)=2k=1nkxkk=1nxkwehavek=0nxk=xn+11x1(x1)k=1nkxk1=nxn+1(n+1)xn+1(x1)2k=1nkxk=x(x1)2(nxn+1(n+1)xn+1)w(x)=2x(x1)2(nxn+1(n+1)xn+1)(11x1)=2x(nxn+1(n+1)xn+1)(x1)2x(1x)(1x)2=2x(nxn+1(n+1)xn+1)+x2x(x1)2f(x)=2nxn+22(n+1)xn+1+x2+x×1x1n(x1)=2nxn+22(n+1)xn+1+x2+xn(x1)(x1)2wedothechangementx1=t(t0)f(x)=f(t+1)=2n(t+1)n+22(n+1)(t+1)n+1+(t+1)2+tntt2wehave(1+t)n+21+(n+2)t+(n+2)(n+1)2t2(1+t)n+11+(n+1)t+(n+1)n2t2(t+1)2+t12n(t+1)n+22(n+1)(t+1)n+1+(t+1)2+t2n{1+(n+2)t+(n+2)(n+1)2t2}2(n+1)(1+(n+1)t+(n+1)n2t2)+1....becontinued...

Answered by mathmax by abdo last updated on 26/Jan/21

in this case it better to use[hospital theorem let  u(x)=(√(x+3x^2  +5x^3 +....+(2n−1)x^n ))−n and v(x)=x−1  u^′ (x)=((1+6x+15x^2 +....+n(2n−1)x^(n−1) )/(2(√(x+3x^2 +5x^3 +....+(2n−1)x^n )))) ⇒  lim_(x→1) u^′ (x)=((1+6+15+....+n(2n−1))/(2(√(1+3+5+....+2n−1))))  v^′ (x)=1 ⇒lim_(x→1) v^′ (x)=1  also  Σ_(k=1) ^n k(2k−1) =2Σ_(k=1) ^n  k^2 −Σ_(k=1) ^n  k =2.((n(n+1)(2n+1))/6)−((n(n+1))/2)  =((n(n+1)(2n+1))/3)−((n(n+1))/2)=n(n+1){((2n+1)/3)−(1/2)}  =n(n+1)(((4n+2−3)/6)) =((n(n+1)(4n−1))/6)  Σ_(k=1) ^n (2k−1) =2Σ_(k=1) ^n k−Σ_(k=1) ^n  k =2((n(n+1))/2)−((n(n+1))/2)  =((n(n+1))/2) ⇒lim_(x→1) (...)  =(((n(n+1)(4n−1))/6)/(2(√((n(n+1))/2)))) =((n(n+1)(4n−1))/(6(√2)(√(n(n+1)))))  =(((4n−1)(√(n(n+1))))/(6(√2)))

inthiscaseitbettertouse[hospitaltheoremletu(x)=x+3x2+5x3+....+(2n1)xnnandv(x)=x1u(x)=1+6x+15x2+....+n(2n1)xn12x+3x2+5x3+....+(2n1)xnlimx1u(x)=1+6+15+....+n(2n1)21+3+5+....+2n1v(x)=1limx1v(x)=1alsok=1nk(2k1)=2k=1nk2k=1nk=2.n(n+1)(2n+1)6n(n+1)2=n(n+1)(2n+1)3n(n+1)2=n(n+1){2n+1312}=n(n+1)(4n+236)=n(n+1)(4n1)6k=1n(2k1)=2k=1nkk=1nk=2n(n+1)2n(n+1)2=n(n+1)2limx1(...)=n(n+1)(4n1)62n(n+1)2=n(n+1)(4n1)62n(n+1)=(4n1)n(n+1)62

Terms of Service

Privacy Policy

Contact: info@tinkutara.com